Theoretical Analysis of an Optical Accelerometer Based on Resonant Optical Tunneling Effect - Aoqun Jian; Chongguang Wei; Lifang Guo; Jie Hu; Jun Tang; Jun Liu; Xuming Zhang; Shengbo Sang (Sensors, 2017)
Acceleration is a significant parameter for monitoring the status of a given objects. This paper presents a novel linear acceleration sensor that functions via a unique physical mechanism, the resonant optical tunneling effect (ROTE). The accelerometer consists of a fixed frame, two elastic cantilevers, and a major cylindrical mass comprised of a resonant cavity that is separated by two air tunneling gaps in the middle. The performance of the proposed sensor was analyzed with a simplified mathematical model, and simulated using finite element modeling. The simulation results showed that the optical Q factor and the sensitivity of the accelerometer reach up to 8.857 × 107 and 9 pm/g, respectively. The linear measurement range of the device is ±130 g. The work bandwidth obtained is located in 10–1500 Hz. The results of this study provide useful guidelines to improve measurement range and resolution of integrated optical acceleration sensors.